Modulation of motor excitability by cortical optogenetic theta burst stimulation. - Chun-Wei Wu; Wen-Tai Chiu; Tsung-Hsun Hsieh; Cho-Han Hsieh; Jia-Jin Jason Chen (PLoS ONE, 2018)
Intermittent theta burst stimulation (iTBS) and continuous theta burst stimulation (cTBS) are protocols used in repetitive transcranial magnetic stimulation (rTMS) or cortical electrical stimulation (CES) to facilitate or suppress corticospinal excitability. However, rTMS and CES excite all types of neuron in the target cortex probed by the coil or electrode, making it difficult to differentiate the effect of TBS on specific neural circuits involved in motor plasticity. In this study, TBS protocols were converted into an optogenetic model to achieve focalized and cell-type-specific cortical modulation. Light-sensitive channelrhodopsin-2 (ChR2) was expressed in the glutamatergic neuron in the primary motor cortex (M1) driven by the CaMKIIα promoter. A custom-made optrode comprising an optical fiber and a metal cannula electrode was fabricated to achieve optogenetic stimulation and simultaneous local field potential (LFP) recording. Single-pulse CES was delivered into M1 to elicit motor-evoked potential (MEP), which served as an indicator of motor excitability, before and after TBS intervention. Results show that both CES-iTBS and optogenetic iTBS (Opto-iTBS) can potentiate MEP activity. However, CES-cTBS suppressed MEP activity whereas Opto-cTBS enhanced it. This discrepancy may have resulted from the different neural networks targeted by the two TBS modalities, with CES-cTBS exciting all types of neuron and Opto-cTBS targeting excitatory neuron specifically. The results support the idea that intra-cortical networks determine the variation of TBS-induced neuroplasticity. This study shows that focalized and cell-type-specific brain stimulation using the optogenetic approach is viable and can be extended for further exploration of neuroplasticity.